Medicinal Chemistry in Secondary School Education — Implementation and Students’ and Teachers’ Attitudes - Štefková, Ivona; Šmejkal, Petr; Kekule, Martina (Scientia in educatione, 2020)
This contribution deals with chemistry education focused on medicinal chemistry at secondary schools and discusses chosen results of questionnaire research made in 2011 and 2013. In the framework of said research, a set of educational materials (educational texts, presentations, worksheets and educational games) was prepared and evaluated, while the main aim of the research was to find opinions and attitudes of participating teachers and students on the theme of medicinal chemistry, and the prepared materials and material applicability in secondary school education. The questionnaire research was done in a framework of cooperation with 25 Czech secondary schools and involved 417 students (230 females and 187 males) and 29 chemistry teachers. The results proved that the attitudes of students as well as teachers to the theme of medicinal chemistry are positive and the theme is considered to be contributive and an important part of secondary school education. In addition to that, the presented materials were also evaluated as of a good quality (regarding their correctness, structure, images etc.) and can be well implemented into secondary school education.